An experimental investigation of steam ejector refrigeration system powered by extra low temperature heat source. (February 2017) - Dong, Jingming; Chen, Xuli; Wang, Weining; Kang, Chunlu; Ma, Hongbin
Abstract: A steam ejector refrigeration system is a low capital cost solution for utilizing industrial waste heat or solar energy. When the heat source temperature is lower than 80 °C, the utilization of the thermal energy from such a low-temperature heat source can be a considerable challenge. In this investigation, an experimental prototype for the steam ejector refrigeration system was designed and manufactured, which can operate using extra low-temperature heat source below 80 °C. The effects of the operation temperature, the nozzle exit position (NXP) and the diameter of the constant area section on the working performance of the steam ejector were investigated at generating temperatures ranging from 40 °C to 70 °C. Three ejectors with a same de Laval nozzle for the primary nozzle and three different constant-area sections were designed and fabricated. The experimental results show that a steam ejector can function for a certain configuration size of the steam ejector with a generating temperature ranging from 40 °C to 70 °C and an evaporating temperature of 10 °C. For a given NXP, the system COP and cooling capacity of the steam ejector decreased until inoperative as the diameter of the constant area section reduced. The results of this investigation provided a good solution for the refrigeration application of the steam ejector refrigeration system powered by an extra low-temperature heat source.